2006
DOI: 10.1007/s00408-005-2563-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing in Nondialyzed Patients with Chronic Renal Failure

Abstract: The prevalence and significance of sleep-disordered breathing (SDB) in dialysis-independent chronic renal failure (CRF) remains unknown. We studied the presence of SDB in nondialyzed CRF patients. Diagnostic polysomnography was performed in consecutive stable nondialyzed CRF patients. Inclusion criteria were age 70% pr, absence of neurologic disease or hypothyroidism, and calculated creatinine clearance <40 ml/min. Thirty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 43 publications
6
66
0
2
Order By: Relevance
“…These results are consistent with the findings of Markou et al (23) but inconsistent with those of Canales et al (24). Markou et al enrolled 35 nondialysis CKD patients (54.3% of the subjects had OSA) with creatinine clearance Ͻ40 ml/min and demonstrated that AHI was significantly correlated with serum urea concentrations but not with creatinine clearance (23). However, their study was limited by its small sample size, with a relatively narrow range of renal function and lack of adjustment for potent covariates including age, BMI, and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with the findings of Markou et al (23) but inconsistent with those of Canales et al (24). Markou et al enrolled 35 nondialysis CKD patients (54.3% of the subjects had OSA) with creatinine clearance Ͻ40 ml/min and demonstrated that AHI was significantly correlated with serum urea concentrations but not with creatinine clearance (23). However, their study was limited by its small sample size, with a relatively narrow range of renal function and lack of adjustment for potent covariates including age, BMI, and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 94%
“…OSAS is reportedly associated with higher risk for stroke, hypertension, diabetes, congestive hearth failure, arrhythmias, and the metabolic syndrome and also with fatal and nonfatal cardiovascular events (4)(5)(6)(7) Previous studies have shown high prevalence of OSA (16 to 54%) in patients with chronic kidney disease (CKD) (8,9). Unruh et al (10) showed that OSA is more common in hemodialysis patients than in general population.…”
mentioning
confidence: 99%
“…Thus dialysis patients have both reduced quantity and quality of sleep. Changes in sleep patterns in advanced CKD patients who are not on dialysis are similar to patients on dialysis (21) …”
Section: Changes In Sleep Architecturementioning
confidence: 92%
“…RLS has been reported in 14-23% in patient on CHD and 20-57% in CKD patients (21,36). The prevalence of PLMD is greater than 50% in CHD and CAPD(see glossary) population (1, 2, [35][36][37][38].…”
Section: Restless Leg Syndrome and Periodic Limb Movement Disordermentioning
confidence: 99%